2015
DOI: 10.1063/1.4934536
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and uncertainty of reversible Markov models

Abstract: Reversibility is a key concept in Markov models and master-equation models of molecular kinetics. The analysis and interpretation of the transition matrix encoding the kinetic properties of the model rely heavily on the reversibility property. The estimation of a reversible transition matrix from simulation data is, therefore, crucial to the successful application of the previously developed theory. In this work, we discuss methods for the maximum likelihood estimation of transition matrices from finite simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(168 citation statements)
references
References 66 publications
3
153
0
Order By: Relevance
“…V D, we reported that MSM time scales differ widely across models constructed from different features. To a lesser extent, this is also the case for time scales predicted by MSMs that have indistinguishable scores; in other words, time scales across indistinguishably good models differ more than their intra-model uncertainties [82][83][84][85][86][87][88] account for. This is likely due to the fact that each model is built from a different state decomposition and is thus describing a (perhaps subtly) different process.…”
Section: Discussionmentioning
confidence: 93%
“…V D, we reported that MSM time scales differ widely across models constructed from different features. To a lesser extent, this is also the case for time scales predicted by MSMs that have indistinguishable scores; in other words, time scales across indistinguishably good models differ more than their intra-model uncertainties [82][83][84][85][86][87][88] account for. This is likely due to the fact that each model is built from a different state decomposition and is thus describing a (perhaps subtly) different process.…”
Section: Discussionmentioning
confidence: 93%
“…This analysis of the systematic bias is based on the approximation of rare transitions between subgraphs in various types of MSMs [eqs. (3), (25), or (59)], which allowed us to proceed with analytical derivations beyond the results previously published in the literature, [23][24][25][26] and obtain the analytical result given by Eq. (64).…”
mentioning
confidence: 99%
“…With detailed balance constraints, the maximum likelihood of Eq. 6 has no closed-form solution but can be iteratively solved (28,62,63).…”
Section: Trammentioning
confidence: 99%